Portal Mi GdO: Propuesta para optimizar el servicio al cliente Gases de Occidente (2023)
This degree project aims to provide a solution to the problem posed by the business challenge of the Master's Degree in Business Management, focused on the case of Gases de Occidente (GdO), a company that distributes and markets natural gas and offers energy solutions in Valle del Cauca and North Cauca. Below, the different key aspects that will be addressed in this report are explored. It begins by analyzing global trends in customer service services of nationally and internationally recognized companies in the provision of public services through benchmarking, taking into account that it is essential to understand how the customer experience evolves, considering aspects such as personalization of care, comfort, accessibility and agility.